Proceedings of the 25th International Conference on Intelligent User Interfaces 2020
DOI: 10.1145/3377325.3377494
|View full text |Cite
|
Sign up to set email alerts
|

Towards making videos accessible for low vision screen magnifier users

Abstract: People with low vision who use screen magnifiers to interact with computing devices find it very challenging to interact with dynamically changing digital content such as videos, since they do not have the luxury of time to manually move, i.e., pan the magnifier lens to different regions of interest (ROIs) or zoom into these ROIs before the content changes across frames.In this paper, we present SViM, a first of its kind screen-magnifier interface for such users that leverages advances in computer vision, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A group of researchers recently developed a screen-magnifier interface that is able to identify salient regions of interest through image processing, and allows the user to control the zoom of the identified (salient) objects with mouse clicks. 52 They tested the device in a study of participants with CVL, and those users expressed a preference for this technique over traditional, simple magnification techniques. Salience-defined magnification centre 52 and giving the viewer the option to turn magnification on and off 50,51 (or up and down) is worthy of future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A group of researchers recently developed a screen-magnifier interface that is able to identify salient regions of interest through image processing, and allows the user to control the zoom of the identified (salient) objects with mouse clicks. 52 They tested the device in a study of participants with CVL, and those users expressed a preference for this technique over traditional, simple magnification techniques. Salience-defined magnification centre 52 and giving the viewer the option to turn magnification on and off 50,51 (or up and down) is worthy of future study.…”
Section: Discussionmentioning
confidence: 99%
“…52 They tested the device in a study of participants with CVL, and those users expressed a preference for this technique over traditional, simple magnification techniques. Salience-defined magnification centre 52 and giving the viewer the option to turn magnification on and off 50,51 (or up and down) is worthy of future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a user study with 13 participants to assess effectiveness of SViM system [6], in which we compared the three prototypes we developed to the Windows screen magnifier [2] and VLC Player magnifier [5]. Both subjective results and our measurements have demonstrated that the users had a better experience with SViM interfaces compared to the baseline magnifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Piano Genie [ 153 ] is an intelligent controller for non-musicians to improvise on the piano. SViM [ 154 ] is an adaptive screen-magnifier tool for people with low vision to watch videos. Lee et al [ 155 ] developed a tool to assess the quality of rehabilitation exercises.…”
Section: Classifying Hcml Researchmentioning
confidence: 99%